2011
DOI: 10.1159/000332582
|View full text |Cite
|
Sign up to set email alerts
|

An Activated Immune and Inflammatory Response Targets the Pancreas of Newborn Pigs with Cystic Fibrosis

Abstract: Background/Aims: In cystic fibrosis (CF), pancreatic disease begins in utero and progresses over time to complete destruction of the organ. Although inflammatory cells have been detected in the pancreas of humans and pigs with CF, their subtypes have not been characterized. Methods: Using four-color flow cytometry, we analyzed the surface antigens of leukocytes in pancreas, blood, and mesenteric lymph nodes (MLN) of newborn pigs with CF (CFTR–/– and CFTRΔF508/ΔF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
(60 reference statements)
3
13
0
Order By: Relevance
“…Our data also support the hypothesis that CF airway hyperinflammation is a direct consequence of lacking functional CFTR rather than an indirect effect of impaired mucociliary clearance and bacterial colonization (Machen, 2006;Ratjen, 2006;Stoltz et al, 2010;Sun et al, 2010). Enhanced inflammatory responses without apparent infection were also found in newborn pigs or infants with CF (Abu- El-Haija et al, 2011;Dakin et al, 2002;Rosenfeld et al, 2001). In addition, experimental restoration of CFTR function in CF cells was shown to decrease the hyperinflammatory state (Eidelman et al, 2001;Van Goor et al, 2006).…”
Section: Discussionsupporting
confidence: 85%
“…Our data also support the hypothesis that CF airway hyperinflammation is a direct consequence of lacking functional CFTR rather than an indirect effect of impaired mucociliary clearance and bacterial colonization (Machen, 2006;Ratjen, 2006;Stoltz et al, 2010;Sun et al, 2010). Enhanced inflammatory responses without apparent infection were also found in newborn pigs or infants with CF (Abu- El-Haija et al, 2011;Dakin et al, 2002;Rosenfeld et al, 2001). In addition, experimental restoration of CFTR function in CF cells was shown to decrease the hyperinflammatory state (Eidelman et al, 2001;Van Goor et al, 2006).…”
Section: Discussionsupporting
confidence: 85%
“…Nonetheless, we note that ANO1 (TMEM16A) overexpression has been shown to suppress proinflammatory cytokine expression in human cystic fibrosis bronchial epithelia (44). Another study identified an activated immune response specific to the pancreas in newborn pigs with cystic fibrosis (45). It seems possible that defects in the ANO1 gene or in its expression in pancreatic islets could affect cytokine expression and evoke an immune response resulting in β cell death.…”
Section: Discussionmentioning
confidence: 84%
“…Further support for the importance of CFTR in maintaining the physiological environment of tissues comes from studies on the pancreas of newborn CF pigs that indicate the presence of increased neutrophil, macrophage, and lymphocyte infiltration in dilated acini and in the interstitium, without an apparent bacterial infection. This suggests the proinflammatory nature of mucus stasis itself (3). Despite these reports, whether loss of CFTR itself or the subsequent infection promotes the inflammatory response remains controversial.…”
Section: Inflammatory Responses In Cf and Copdmentioning
confidence: 99%